Does Target Firm's Earnings Management Affect Shareholder's Gains? Evidence from China - Azhar Mughal; Abdul Haque; Zohaib Zahid; Furman Ali; Zheng Li (Credit and Capital Markets – Kredit und Kapital, 2022)
This study tests the hypothesis that the target firms are involved in earnings management activities in quarters leading to a takeover announcement. Using a sample of 3,455~Chinese listed firms that are targets of successful acquisitions over the period 2007–2020, and for a matched sample of non-targets, we find that target firms manipulate earnings in quarters leading to the announcement date. Further, we find evidence of a negative relationship between earnings management and short-term gains to shareholders. Our result remains robust after controlling for various deal characteristics. The study also suggests that pre-merger earnings management in target firms is not fully anticipated by the market before the takeover announcement. We find no evidence of earnings management immediately after the announcement quarter.
Keywords: G14; G34; M41; 330; Earnings Management; Takeovers; Short-Term Gains